Mathematical Modeling of Pollution Transfer in Open Channel - Martyniuk, Petro; Ostapchuk, Oksana; Nalyvaiko, Vitalii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The problem of pollution transfer by water flow in open channel was considered. The mathematical model of the problem was constructed. The numerical solution of the onedimensional boundary problem was obtained. The computational algorithm for solving the problem was programmed to implement. A series of numerical experiments with their further analysis was conducted.